TECTONOSTRATIGRAPHY OF THE EASTERN PART OF SULAWESI,INDONESIA. IN RELATION TO THE TERRANE ORIGINS - Surono Martosuwito (Pusat Survei Geologi, 2012)
Geologically the eastern part of Sulawesi is the one of the most complex area in Indonesia. It is formed by two difference composition and origin terranes: ophiolite complex and its pelagic sediment cover and continental terranes, both covered by Sulawesi molasse. The ophiolite and pelagic sedimentary cover had been thrusted over the continental terranes during Late Oligocene-Middle Miocene. After the collision, the Sulawesi molasse was unconformably deposited. The ophiolite was formed in a mid-oceanic ridge, within the Pacific Plate. The continental terranes, in the other hand, were originated from the northern margin of the Australian Continent.Key words: Continental fragment, ophiolite, terrane, and origin